Comparison of intra-procedural vs. post-stenting prolonged bivalirudin infusion for residual thrombus burden in patients with ST-segment elevation myocardial infarction undergoing: the MATRIX (Minimizing Adverse Haemorrhagic Events by TRansradial Access Site and angioX) OCT study. (28th March 2019) - Garcia-Garcia, Hector M; Picchi, Andrea; Sardella, Gennaro; Adamo, Marianna; Frigoli, Enrico; Limbruno, Ugo; Rigattieri, Stefano; Diletti, Roberto; Boccuzzi, Giacomo; Zimarino, Marco; Contarini, Marco; Russo, Filippo; et al.
Abstract: Aims: To compare prolonged bivalirudin infusion vs. an intra-procedural only bivalirudin infusion administration in subjects with ST-segment elevation myocardial infarction (STEMI) regarding residual stent strut thrombosis. Methods and results: Multivessel STEMI patients undergoing primary percutaneous coronary intervention (PPCI) and scheduled for a staged percutaneous coronary intervention (PCI) before hospital discharge were selected among those allocated to either prolonged bivalirudin or intra-procedural only bivalirudin infusion in the MATRIX (Minimizing Adverse Haemorrhagic Events by TRansradial Access Site and angioX) Treatment-Duration study. Optical coherence tomography (OCT) of the infarct-related artery was performed at the end of PPCI and 4–5 days thereafter during staged intervention. The predefined endpoint was the percentage difference in the number of stent cross-sections with a thrombotic area >5% at the end of PPCI and at the time of staged PCI (ΔThCS). Between September 2013 and November 2015, 137 were randomized to either intra-procedural only bivalirudin infusion ( N = 64) or prolonged bivalirudin ( N = 73) at 16 European sites. Mean stent area, minimum lumen area, percentage of malapposed struts, and mean percent thrombotic area were comparable after index or staged PCI. The difference in the proportion of frames with percent thrombotic area >5% (ΔTh > 5%) were −7.7 (−22.1 to 5.1) in the intra-procedural bivalirudin infusion group and −8.8 (−23.1 to 2.6) in the prolonged infusion group ( P = 0.994). Time from index to follow-up OCT imaging and the infarct vessel artery did not affect this OCT-based endpoint. Conclusion: A strategy of prolonged bivalirudin infusion after PPCI did not reduce residual stent strut thrombosis when compared with intra-procedural only bivalirudin infusion administration (funded by The Medicines Company and Terumo; MATRIX ClinicalTrials.gov number, NCT01433627).